A Between-Subjects Test of the Lower-Identification/Higher-Priming Paradox. (March 2013) - Rubino, I Alex; Rociola, Giuseppe; Di Lorenzo, Giorgio; Magni, Valentina; Ribolsi, Michele; Mancini, Valentina; Saya, Anna; Pezzarossa, Bianca; Siracusano, Alberto; Suslow, Thomas
An under-recognised U-shaped model states that unconscious and conscious perceptual effects are functionally exclusive and that unconscious perceptual effects manifest themselves only at the objective detection threshold, when conscious perception is completely absent. We tested the U-shaped line model with a between-subjects paradigm. Angry, happy, neutral faces, or blank slides were flashed for 5.5 ms and 19.5 ms before Chinese ideographs in a darkened room. A group of volunteers ( n = 84) were asked to rate how much they liked each ideograph and performed an identification task. According to the median identification score two subgroups were composed; one with 50% or <50% identification scores ( n = 31), and one with above 50% identification scores ( n = 53). The hypothesised U-shaped line was confirmed by the findings. Affective priming was found only at the two extreme points: the 5.5 ms condition of the low-identification group (subliminal perception) and the 19.5 ms condition of the >50% high-identification group (supraliminal perception). The two intermediate points (19.5 ms of the low-identification group and 5.5 ms of the high-identification group) did not correspond to significant priming effects. These results confirm that a complete absence of conscious perception is the condition for the deployment of unconscious perceptual effects.